Use of Punctuation in Primary School - Surayyokhon Jurahonova Abduakhatkhanovna (Zien Journals, 2022)
The article provides feedback on improving the spelling literacy of primary school students, teaching them the rules of punctuation
Keywords: communicative literacy; oral and written form; consistency in education; spelling